Central Auditory Function - Zenker Castro, Franz; Barajas del Prat, José Juan (Auditio, 2021)
Central Auditory Processing Disorders (CAPD) result from a deficit in sensory processing that affects listening, speech understanding, and learning. These deficits are the product of the inability or lack of ability to attend, discriminate, recognize or understand information of auditory origin. The study of central auditory functions is complex since it does not constitute a unitary entity attributable to a single nosological category. The deficits observed in the processing of auditory information at the central level can be expressed in very different ways and respond to multiple etiologies. The study of hearing as a central phenomenon implies an approach from a functional perspective that requires an approach to hearing as a process and extensive knowledge about the functional anatomical correspondences of hearing. Audiological evaluation of these disorders includes the use of psychoacoustic and electrophysiological tests selected according to the patient's medical history. The proposed interventions for patients diagnosed with CAPD are based on the use of central resources in the improvement of linguistic and cognitive abilities, development of auditory-linguistic skills, development of metalanguage, use of compensatory strategies, and development of listening and metacognition strategies.